Patents and regulatory exclusivities on FDA-approved insulin products: A longitudinal database study, 1986-2019. - Anders Olsen; Reed F Beall; Ryan P Knox; Sean S Tu; Aaron S Kesselheim; William B Feldman (PLoS Medicine, 2023)
Background Insulin is the primary treatment for type 1 and some type 2 diabetes but remains costly in the United States, even though it was discovered more than a century ago. High prices can lead to nonadherence and are often sustained by patents and regulatory exclusivities that limit competition on brand-name products. We sought to examine how manufacturers have used patents and regulatory exclusivities on insulin products approved from 1986 to 2019 to extend periods of market exclusivity. Methods and findings We used the publicly available Food and Drug Administration (FDA) Approved Drug Products with Therapeutic Equivalence Evaluations (Orange Book) to identify all approved biosynthetic insulin products. Individual products approved under the same New Drug Application (NDA)-e.g., a vial and pen-were considered as separate products for the purposes of analysis. We recorded all patents and regulatory exclusivities listed in the Orange Book on each product and used Google Patents to extract the timing of patent application and whether patents were obtained on delivery devices or others aspects of the product. The primary outcome was the duration of expected protection, which was determined by subtracting the FDA approval date for each product from its last-to-expire patent or regulatory exclusivity (whichever occurred later). We performed a secondary analysis that considered overall protection on insulin lines-defined as groups of products approved under the same NDA with the same active ingredients manufactured by the same company. We also examined competition from follow-on insulin products-defined as products approved with the same active ingredients as originators but manufactured by different companies (approved via a specific drug approval pathway under section 505(b)(2) of the Food, Drug, and Cosmetic Act). During the study period, the FDA approved 56 individual products across 25 different insulin lines and 5 follow-ons across 3 different insulin lines. Thirty-three (59%) of the 56 products were drug-device combinations. Manufacturers of 9 products approved during the study period obtained patents filed after FDA approval that extended their duration of expected protection (by a median of 6 years). Approximately 63% of all patents on drug-device combinations approved during the study period were related to delivery devices. The median duration of expected protection on insulin products was 16.0 years, and the median protection on insulin lines was 17.6 years. An important limitation of our analysis is that manufacturers may continue to add patents on existing insulin products while competitors may challenge patents; therefore, periods of protection may change over time. Conclusions Among several strategies that insulin manufacturers have employed to extend periods of market exclusivity on brand-name insulin products are filing patents after FDA approval and obtaining a large number of patents on delivery devices. Policy reforms are needed to promote timely competition in the pharmaceutical market and ensure that patients have access to low-cost drugs.